Eksistensi Muhammadiyah Dalam Pengembangan Kompetensi Guru - Ory Syafari Jamel Sutiyan; Dolly Riri Ramdhanu Jamel Sutiyan; Adlin Adlin; Dedy Irawan; Muchamad Arif Al Ardha (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Muhammadiyah Existence In Teacher Competence DevelopmentMuhammadiyah is one of the largest Islamic organizations in Indonesia which has a revolutionary contribution in the field of Islamic education. Circulation of news about sexual harassment, abuse by teachers against students. Then the phenomenon of Muhammadiyah's members not sending their children to Muhammadiyah schools is an important issue behind this research. This makes the competence of Muhammadiyah teachers is important to noticed because of the large influence and quantity of students. Therefore, this paper purposed to learn about the existence of Muhammadiyah in developing the teacher competence. This study was compiled using qualitative methods by interviewing several Muhammadiyah figures in Riau Province and conducting triangulation as data validity. In addition, the library approach collects various sources of relevant and comprehensive information. The results of this research show that Muhammadiyah has contributed to the development of teacher quality and competence by issuing normative rules, directives, books and other guidelines such as the Guidebook for Islamic Life for Muhammadiyah Citizens (PHIWM Book), forming social groups such as MGMP teacher associations and FGM, even training and the regeneration proses at Muhammadiyah orthonomous organizations (Muhammadiyah Youth, KORPS Mubaligh, Naisyatul Aisyiyah, etc.) can build and improving the competence of teachers and Muhammadiyah member. However, efforts to develop the competence of Muhammadiyah teachers do not always succeed, it caused lack of funding, lack of competence of Muhammadiyah leaders at lower levels, lack of Teacher awareness, and limited facilities and infrastructure. So that the guidelines and rules that have been formulated by the Muhammadiyah's Central Leadership are difficult to applicated into a comprehensive program.Abstract: Eksistensi Muhammadiyah Dalam Pengembangan Kompetensi Guru. Muhammadiyah merupakan salah satu organisasi islam terbesar di Indonesia yang memiliki kontribusi revolusioner dalam bidang pendidikan islam. Beredarnya berita tentang pelecehan, penganiayaan yang dilakukan guru kepada siswa. Kemudian fenomena pengurus yang tidak menyekolahkan anaknya di sekolah Muhammadiyah menjadi isu penting yang melatarbelakangi penelitian ini. Hal tersebut membuat kompetensi guru Muhammadiyah menjadi penting untuk diperhatikan mengingat besarnya pengaruh dan kuantitas peserta didik yang diajar. Oleh sebab itu penelitian ini bertujuan untuk membahas eksistensi Muhammadiyah dalam mengembangkan pendidikan islam pada aspek yang lebih khusus yaitu kompetensi guru. Penelitian ini disusun menggunakan metode kualitatif dengan mewawancarai beberapa tokoh Muhammadiyah di Provinsi Riau serta melakukan triangulasi sebagai validitas data. Selain itu, pendekatan pustaka dengan mengumpulkan berbagai sumber informasi yang relevan dan komprehensif. hasil telaah berbagai sumber informasi menunjukkan bahwa Muhammadiyah sudah berkontribusi dalam pengembangan kualitas dan kompetensi guru dengan menerbitkan aturan, arahan, buku dan pedoman lain secara normatif seperti Buku Pedoman Hidup Islami Warga Muhammadiyah (PHIWM), membentuk kelompok sosial seperti perkumpulan guru MGMP dan FGM, bahkan pelatihan dan proses kaderisasi organisasi otonom Muhammadiyah (Pemuda Muhammadiyah, KORPS Mubaligh, Nasyiatul Aisyiyah, dll) dapat membentuk kompetensi guru dan kader Muhammadiyah. Namun ikhtiar pengembangan kompetensi guru Muhammadiyah tidak selalu dapat berjalan dengan baik, antara lain disebabkan oleh faktor pendanaan, kompetensi pimpinan Muhammadiyah tingkat bawah, kesadaran guru; dan faktor sarana dan prasarana yang terbatas.